The role of the teacher in the university-society integration. - Mayra Sofia Gil (Medisur, 2004)
The aim of the medical university is to develop professionals with high moral values and an elevated qualification, able to face the always increasing and continuous demands of science, technology and society, aim that is achieved by means of the teaching learning process in which professors play a decisive role which is at the same time present in all the components of the process with a permanent example in the decisive contribution for improving quality and excellence at the university. In order to guarantee quality, excellence and pertinence of the medical university, the professor should represent a paradigm which shows qualities such as integrity capacity, communication, investigator, revolutionary, reflexive and compromised with homeland and society.